2020
DOI: 10.1021/acsanm.9b02542
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-Coated Silicon Nanopillars as Ultra-Broadband and Thermally Robust Solar Harvesting Materials

Abstract: Solar harvesting materials or structures, with broadband optical absorption, high-temperature tolerance, and scalable fabrication processes, have attracted much attention for real-life optical applications, such as in solar energy harvesting and solar thermophotovoltaic devices. In the present work, a refractory tungsten-based absorber is proposed that exhibits a high optical absorption above 95% over the AM 1.5 G spectrum (220−2600 nm) and up to 98.5% in the visible light range. This broadband absorber is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…67 Although the UV−NIR absorbance capacity of the fs-5W-W-600 °C sample is lower than that of Al 2 O 3 /W/Al 2 O 3 / W/Si metal−insulator−metal (MIM) resonators, 68 hierarchical LIPSS/NPs structures of the fs-5W-W-600 °C sample presented in this work excel at high absorbance in a much broader light band. One of the best W-based ultrabroad absorbers is tungstencoated Si nanopillars with >95% absorbance in the 220−2600 nm range, 69 which were produced by five procedures including spin coating, polystyrene sphere (PS) lithography, magnetron sputtering, metal-assisted chemical etching (MACE), and atomic layer deposition (ALD). Compared with this work, the absorbers prepared by fs laser ablation and thermal oxidation annealing are much simpler, based on which the diversity of WO 3−x interfacial structures can be enriched.…”
Section: Resultsmentioning
confidence: 99%
“…67 Although the UV−NIR absorbance capacity of the fs-5W-W-600 °C sample is lower than that of Al 2 O 3 /W/Al 2 O 3 / W/Si metal−insulator−metal (MIM) resonators, 68 hierarchical LIPSS/NPs structures of the fs-5W-W-600 °C sample presented in this work excel at high absorbance in a much broader light band. One of the best W-based ultrabroad absorbers is tungstencoated Si nanopillars with >95% absorbance in the 220−2600 nm range, 69 which were produced by five procedures including spin coating, polystyrene sphere (PS) lithography, magnetron sputtering, metal-assisted chemical etching (MACE), and atomic layer deposition (ALD). Compared with this work, the absorbers prepared by fs laser ablation and thermal oxidation annealing are much simpler, based on which the diversity of WO 3−x interfacial structures can be enriched.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, various spectrally selective emitters with different structures have been studied, 10 including blazed gratings [11][12][13] or fishnet gratings, 14 micro-cavities, 15 2D [16][17][18] or 3D photonic crystals, 19 and metamaterials. [20][21][22][23][24][25] Actually, according to Wien's displacement law, the surface temperature of thermal emitters in STPV systems is generally over 1000 K, 20 so practical thermal emitters are generally constructed of refractory materials, 26 such as titanium nitride (TiN), [27][28][29][30][31] nickel (Ni), 32,33 titanium (Ti), 34,35 chromium (Cr), 36,37 tungsten (W), 2,23,[38][39][40][41][42] tantalum (Ta), 16,43 and Mo. 44,45 For example, S. L. Wu et al 29…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various spectrally selective emitters with different structures have been studied, 10 including blazed gratings 11–13 or fishnet gratings, 14 micro-cavities, 15 2D 16–18 or 3D photonic crystals, 19 and metamaterials. 20–25 Actually, according to Wien's displacement law, the surface temperature of thermal emitters in STPV systems is generally over 1000 K, 20 so practical thermal emitters are generally constructed of refractory materials, 26 such as titanium nitride (TiN), 27–31 nickel (Ni), 32,33 titanium (Ti), 34,35 chromium (Cr), 36,37 tungsten (W), 2,23,38–42 tantalum (Ta), 16,43 and Mo. 44,45 For example, S. L. Wu et al 29 demonstrated a TiN-based metasurface selective absorber fabricated through continuously variable spatial frequency photolithography, and a calculated average absorption of 87% from 250 nm to 2300 nm and 29% in the wavelength range of 5 μm–13 μm was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Sakurai et al [34] embedded a tungsten nanosphere array in a dielectric layer, achieving the α tot of 0.896 and the η of 85.3% at 1000 K and 86.3 suns. Hou et al [35] designed an absorber that consists of a cylindrical SiO 2 array coated by tungsten and Al 2 O 3 , which can achieve the α tot of above 0.95 and keep stable under 1300 K. Ye et al [36] proposed an absorber using a nanosphere-nanocuboid array, obtaining the α tot of 0.9535 and the η of 87.56% under 1000 K and 100 suns. Xu et al [37] fabricated an absorber that employs a tungsten nanodisc array on a SiO 2 /W basis, and the average α λ is 0.90 within 0.5-1.75 μm.…”
Section: Introductionmentioning
confidence: 99%